2008
DOI: 10.1021/bi801056w
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Gs-Coupled Receptors in Smooth Muscle Exhibit Differential Susceptibility to GRK2/3-Mediated Desensitization

Abstract: Although G protein-coupled receptor (GPCR) kinases (GRKs) have been shown to mediate desensitization of numerous GPCRs in studies using cellular expression systems, their function under physiological conditions is less well understood. In the current study, we employed various strategies to assess the effect of inhibiting endogenous GRK2/3 on signaling and function of endogenously expressed Gs-coupled receptors in human airway smooth muscle (ASM) cells. GRK2/3 inhibition by expression of a Gβγ sequestrant, a G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
54
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 57 publications
4
54
0
Order By: Relevance
“…Mak and coworkers have indicated that decreasing the expression of GRK-2 within the airways may lessen b 2 -AR desensitization (30). This observation is supported by a recent study from Kong and colleagues, which reported that inhibition of endogenous GRK2 and GRK3 in ASM is associated with increases in b 2 -AR acute signaling (31). Together, these results indicate that repeated bouts of moderate-intensity aerobic exercise may attenuate AHR by decreasing GRK-2-mediated desensitization of b 2 -AR.…”
Section: Discussionmentioning
confidence: 79%
“…Mak and coworkers have indicated that decreasing the expression of GRK-2 within the airways may lessen b 2 -AR desensitization (30). This observation is supported by a recent study from Kong and colleagues, which reported that inhibition of endogenous GRK2 and GRK3 in ASM is associated with increases in b 2 -AR acute signaling (31). Together, these results indicate that repeated bouts of moderate-intensity aerobic exercise may attenuate AHR by decreasing GRK-2-mediated desensitization of b 2 -AR.…”
Section: Discussionmentioning
confidence: 79%
“…There is indeed evidence that human EP4 receptors can be phosphorylated by GRK2 (Neuschäfer-Rube et al, 1999). Conversely, PGE 2 -induced cAMP production in smooth muscle cells is unaffected in conditions of low GRK2 (Kong et al, 2008). We cannot exclude that low GRK2 in nociceptors has an additional effect upstream of cAMP, e.g., at the level of G-protein coupling to the receptor (Dina et al, 2009).…”
Section: Discussionmentioning
confidence: 89%
“…Our previously published studies demonstrated that PGE2 promotes the cAMP-dependent activation of PKA and phosphorylation of VASP in HASM cells via the prostaglandin E2 (EP2) receptor (25,26), which, in contrast to b 2 AR, is relatively resistant to agonist-specific desensitization. Indeed, the accumulation of cAMP and of PKA during both acute and chronic with agonists were markedly greater with PGE2 compared with b 2 AR agonists (14,(25)(26)(27)(28) with regard to greater efficiency in the inhibition of HASM cell growth (26,29) and migration (6). Indeed, our published data show that, in contrast to b 2 AR agonists that transiently increase the phosphorylation of VASP but decrease in effectiveness by 3 hours, PGE2 promotes a PKA-dependent phosphorylation of VASP that is sustained for up to 18 hours, suggesting that prolonged exposure to PGE2 does not desensitize EP2 receptors (25).…”
Section: Discussionmentioning
confidence: 99%
“…Such differences between b-agonists and PGE2 may be explained by differential mechanisms of b 2 AR and EP2 receptor desensitization in HASM cells. Our previous data demonstrate that, in HASM cells, the desensitization of the b 2 AR receptor is selectively mediated by G proteincoupled receptor kinases 2/3 (GRK2/3) that exert little effect on EP2 receptor functions (26).…”
Section: Discussionmentioning
confidence: 99%